2016
DOI: 10.1002/stem.2361
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Apoptotic Cell-Based Therapies–Rationale, Preclinical Results and Future Clinical Developments

Abstract: The objectives of this review are to summarize the experimental data obtained using apoptotic cell-based therapies, and then to discuss future clinical developments. Indeed, apoptotic cells exhibit immunomodulatory properties that are reviewed here by focusing on more recent mechanisms. These immunomodulatory mechanisms are in particular linked to the clearance of apoptotic cells (called also efferocytosis) by phagocytes, such as macrophages, and the induction of regulatory T cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 81 publications
0
59
0
1
Order By: Relevance
“…Several studies have demonstrated the induction of immune tolerance in different settings in response to DC phagocytosis of apoptotic cells (reviewed in (63, 64)). The therapeutic potential of apoptotic cell induced immunosuppression has been explored based on data in animal models demonstrating effective control of chronic inflammation in the settings of allograft rejection and graft- versus -host disease (65, 66), diabetes (67), arthritis (6871), septic shock (72), and other chronic and acute inflammatory conditions (reviewed in (73)). A recently completed phase I/IIa clinical trial concluded that a single infusion of early apoptotic donor cells to 13 patients with hematological malignancies a day prior to hematopoietic stem cell transplantation, is a safe and potentially effective prophylactic therapy for acute graft- versus -host disease (74).…”
Section: Suppression Of Inflammation and Immune Response By Apoptoticmentioning
confidence: 99%
“…Several studies have demonstrated the induction of immune tolerance in different settings in response to DC phagocytosis of apoptotic cells (reviewed in (63, 64)). The therapeutic potential of apoptotic cell induced immunosuppression has been explored based on data in animal models demonstrating effective control of chronic inflammation in the settings of allograft rejection and graft- versus -host disease (65, 66), diabetes (67), arthritis (6871), septic shock (72), and other chronic and acute inflammatory conditions (reviewed in (73)). A recently completed phase I/IIa clinical trial concluded that a single infusion of early apoptotic donor cells to 13 patients with hematological malignancies a day prior to hematopoietic stem cell transplantation, is a safe and potentially effective prophylactic therapy for acute graft- versus -host disease (74).…”
Section: Suppression Of Inflammation and Immune Response By Apoptoticmentioning
confidence: 99%
“…Apoptotic cells exert immunomodulatory effects either by releasing active immune mediators directly or indirectly via the modulation of phagocytes and dendritic cells [52]. The infusion of apoptotic cells attenuates systemic concentrations of inflammatory cytokines [53,54] Pigs receiving apoptotic cell secretome had an ejection fraction (57.0 versus 40.5 %), improved cardiac output (4.0 versus 2.4 L/min), and reduced infarct area (12.6 versus 6.9 %) compared to controls (see Table 2).…”
Section: Apoptosis and The Rise Of The Phoenix Signaling Pathwaymentioning
confidence: 99%
“…Apoptotic cells exert immunomodulatory effects either by releasing active immune mediators directly or indirectly via the modulation of phagocytes and dendritic cells [52]. The infusion of apoptotic cells attenuates systemic concentrations of inflammatory cytokines [53, 54], whereas anti-inflammatory cytokines, such as IL-10 [5557] and/or TGF-β [53, 57], are released.…”
Section: Apoptosis and The Rise Of The Phoenix Signaling Pathwaymentioning
confidence: 99%
“…Based on the immunomodulatory capacities of apoptotic cells during the last decade, several pre-clinical studies evaluated their usage for the treatment of autoimmune disease or organ transplantation (Table 1) (reviewed in [52]).…”
Section: Pre-clinical Application Of Nucleated Apoptotic Cellsmentioning
confidence: 99%
See 1 more Smart Citation